Can Investor Attention Predict Cryptocurrency Returns? : On the interconnections of the cryptocurrency market - Ahtinen, Juuso (My University, 2020)
The purpose of this thesis is to study the predictability of cryptocurrency returns by investor attention, the interconnections of the cryptocurrency market, and what causes attention to cryptocurrencies. This is done by examining Bitcoin, Ethereum and Ripple which are the three biggest cryptocurrencies by market capitalization in January 2020. The dataset is constructed from weekly returns, weekly changes in investor attention measured by Google trend data and weekly changes in average weekly trading volume between years 2016 and 2019. The empirical analysis is conducted by performing OLS regressions, vector autoregressions and Granger causality tests. Additional robust tests are conducted by dividing the sample in pre-bubble and post-bubble samples adding all of the investor attention proxies to individual Cryptocurrency regressions. The results suggest that the market phase for a cryptocurrency affects the predictability of returns as the statistically significant positive relationship between investor attention disappears in the post-bubble sample for Bitcoin and Ethereum but endures for Ripple in both samples. This provides more evidence for the earlier findings that cryptocurrencies become more efficient as the market matures. The interconnections of the cryptocurrency market are shown to exist as the returns of Bitcoin drive investor attention to Ripple which is shown to be a significant predictor for all of the three cryptocurrencies in the whole sample. The spillover effect is shown to take time confirming earlier findings and unfolding the herding effect via investor attention in cryptocurrencies. Additionally, investor attention is shown to be caused by earlier returns for the cryptocurrency as well as the returns of Bitcoin. These results explain the interconnections of cryptocurrencies, the changing market dynamics in the cryptocurrency market, and the predictability of cryptocurrency returns by investor attention.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance